Internet surveillance, regulation, and chilling effects online: a comparative case study - Jonathon W. Penney (Internet Policy Review, 2017)
With internet regulation and censorship on the rise, states increasingly engaging in online surveillance, and state cyber-policing capabilities rapidly evolving globally, concerns about regulatory "chilling effects" online—the idea that laws, regulations, or state surveillance can deter people from exercising their freedoms or engaging in legal activities on the internet have taken on greater urgency and public importance. But just as notions of "chilling effects" are not new, neither is skepticism about their legal, theoretical, and empirical basis; in fact, the concept remains largely un-interrogated with significant gaps in understanding, particularly with respect to chilling effects online. This work helps fill this void with a first-of-its-kind online survey that examines multiple dimensions of chilling effects online by comparing and analyzing responses to hypothetical scenarios involving different kinds of regulatory actions—including an anti-cyberbullying law, public/private sector surveillance, and an online regulatory scheme, based on the Digital Millennium Copyright Act (DMCA), enforced through personally received legal threats/notices. The results suggest not only the existence and significance of regulatory chilling effects online across these different scenarios but also evidence a differential impact—with personally received legal notices and government surveillance online consistently having the greatest chilling effect on people's activities online—and certain online activities like speech, search, and personal sharing also impacted differently. The results also offer, for the first time, insights based on demographics and other similar factors about how certain people and groups may be more affected than others, including findings that younger people and women are more likely to be chilled; younger people and women are less likely to take steps to resist regulatory actions and defend themselves; and anti-cyberbullying laws may have a salutary impact on women's willingness to share content online suggesting, contrary to critics, that such laws may lead to more speech and sharing, than less. The findings also offer evidence of secondary chilling effects— where users' online activities are chilled even when not they, but others in their social networks receive legal processes.
Keywords: 300; Chilling effects; Online surveillance; Government surveillance; Corporate surveillance